2022
DOI: 10.1088/1741-4326/ac5450
|View full text |Cite
|
Sign up to set email alerts
|

ARC reactor neutronics multi-code validation*

Abstract: The affordable, robust, compact (ARC) reactor is a tokamak fusion reactor concept currently under development by Commonwealth Fusion Systems (CFS)and Massachusetts Institute of Technology. There are three important neutronics considerations for the operation of the ARC reactor: (1) breeding of enough tritium in the blanket to sustain the D-T reaction in the plasma; (2) ensuring low fluence on the superconducting toroidal field coils; and (3) assessing neutron volumetric heating in structural component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Considering an isotropic neutron emission, the toroidal geometry imposes a 1/r radial decrease of the fluence from the FW outwards, since the particles distribute approximately over the surface area of a torus. Despite the fact that the spectrum and fluences obtained here are in reasonable agreement with those from three-dimensional simulations of a similar design [19], it is important to highlight that fine features of the spectra and fluences in different regions of the magnet system can only be captured with a full geometry implementation. Considering the spatial constraints in the design, a precise knowledge of the radiation damage over the volume of the magnet will be necessary to optimize the shielding design.…”
Section: Monte Carlo Simulationssupporting
confidence: 53%
“…Considering an isotropic neutron emission, the toroidal geometry imposes a 1/r radial decrease of the fluence from the FW outwards, since the particles distribute approximately over the surface area of a torus. Despite the fact that the spectrum and fluences obtained here are in reasonable agreement with those from three-dimensional simulations of a similar design [19], it is important to highlight that fine features of the spectra and fluences in different regions of the magnet system can only be captured with a full geometry implementation. Considering the spatial constraints in the design, a precise knowledge of the radiation damage over the volume of the magnet will be necessary to optimize the shielding design.…”
Section: Monte Carlo Simulationssupporting
confidence: 53%
“…For both the ambitious and moderate t d targets, TBR r is well within the expected achievable range (<1.15) if FC and PO technologies improve with respect to the baseline case. The neutronics analysis carried out by Bae et al [17] reported a TBR a = 1.053 for an Inconel-718 VV in ARC. A similar result is reported in [11], which used a simplified neutronics model of an ARC-class plant and calculated a TBR a = 1.07.…”
Section: Implications For Arc-class Tokamak Design and Operationsmentioning
confidence: 99%
“…It also provides efficient heat conduction away from the coupled first wall (FW)-VV structure, which is very important at the high power density ARC proposes. Analyses of ARC have been carried out in the fields of materials science [10][11][12], thermal analysis [13][14][15], neutronics [13,[16][17][18], and plasma physics [2,13,19].…”
Section: Introductionmentioning
confidence: 99%
“…Power extraction and tritium breeding is fulfilled by a liquid breeding blanket consisting of a low-pressure, slow-flowing lithium beryllium fluoride molten salt (FLiBe) contained in a tank that surrounds the vacuum vessel. A TBR > 1 has been computed for different structural and functional materials in the LIB (Segantin et al, 2020;Bae et al, 2022). A classic thermodynamic cycle converts the thermal power extracted from the blanket to electricity.…”
Section: Commonwealth Fusion Systemsmentioning
confidence: 99%